Dampak Pelatihan “Count Me In” Bagi Penguatan Kerelawanan (Volunteering) dalam Civil Society Organization (CSO) - Adiyati Fathu Roshonah; Tjahjo Suprajogo; Agus Yuniawan Isyanto; Diah Andika Sari (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2020)
Public education has a strategic position in developing human resources and encouraging the improvement of the quality of education through the principle of lifelong education. Although the scope is not as intensive as formal education, its role cannot ignore in the effort to educate the nation's life. Community education involves many individuals in Civil Society Organizations (CSO). One way to increase the capacity and capability of human resources in organizations is through training activities (training). NICE Foundation Indonesia has filled out Count Me In Training for volunteers who have been contributing to community education. This study conduct to evaluate the Count Me In Training of 10 (ten) CSOs using the Kirkpatrick & Kirkpatrick Four Level Evaluation Model. The results showed objectives Count Me In Training achieved as evidenced by an increase in knowledge and changes in the behaviour of participants, as well as an increase in individual and organizational performance in volunteerism management